A simple method for fabricating phase-shifted fibre Bragg gratings with flexible choice of centre wavelength - Chehura, Edmon; James, Stephen W.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2009)
A simple technique for fabricating phase-shifted fibre Bragg gratings (PSFBGs) without the use of a phase-shifted phase mask is presented. Two, 3-mm long, standard fibre Bragg gratings (FBGs) were inscribed sequentially in singlemode fibre at the same Bragg wavelength such that the FBGs physically overlapped by one grating period. This induces a spectral-hole in the middle of the reflection spectrum of a standard FBG, equivalent to a π-phase shifted FBG. The flexibility of the technique in writing PSFBGs at any choice of wavelength is demonstrated. The results show that PSFBG devices produced by this method are highly reproducible and the process is fast